The Impact of Trust in Platform Providers on User Participation and Economic Benefits in the Sharing Economy in Indonesia - Akadji, Irfan; Marliani, Gusti; Laksono, Muflih Adi (Eastasouth Institute, 2024)
This research investigates the effect of trust in platform providers on user participation and economic benefits in the sharing economy within the context of Indonesia. Utilizing a quantitative approach, Structural Equation Modeling (SEM) with Partial Least Squares (PLS) path analysis was employed to analyze data collected from a sample of 150 participants. The measurement model assessment confirmed the reliability and validity of the latent constructs, while the structural model estimation revealed significant positive relationships between trust in platform providers and user participation, trust in platform providers and economic benefits, as well as user participation and economic benefits. Mediation analysis further demonstrated the mediating role of user participation in the relationship between trust in platform providers and economic benefits. The moderation analysis did not reveal any significant moderation effects. Overall, the findings contribute to understanding the dynamics of trust, user behavior, and economic outcomes in the Indonesian sharing economy context, offering insights for platform providers, policymakers, and researchers.